Examining the Potential of a University-Accredited Islamic Education Teacher Training Program: A Conceptual Exploration - Asma Ahmed (Education Sciences)
Public schools (K-12) are experiencing a remarkable decline in enrollment across Canada. More and more parents are choosing independent schools for their children’s education. Muslim parents, in particular, are transferring their children to Islamic schools as they are increasingly losing faith in public schools. Muslim students in the public school systems, wherever they are on the continuum of practice—from secular to orthodox—do not perceive their schools to be responsive to their religious beliefs, values, behaviours, and practices. However, Islamic schools are stuck in normative, secular, and reductive pedagogies, with most, if not all, Islamic teachers lacking training in Islamic pedagogy. This article is a conceptual exploration of various approaches to offering an Islamic teacher training program in Canada by an accredited university, including reintroducing the Islamic Teacher Education Programme (ITEP), which offered a one-year professional learning certificate. Another approach is establishing a stream in teacher education programs similar to the Catholic stream. The article serves as a stepping stone to initiate dialogue and collaborative efforts toward creating a comprehensive approach that includes all stakeholders tailored to the unique needs of Islamic school teachers in Ontario, Canada.